Upgrading Organic Compounds through the Coupling of Electrooxidation with Hydrogen Evolution - Chen, Guangbo; Li, Xiaodong; Feng, Xinliang (Angewandte Chemie International Edition, 2022)
The electrocatalytic splitting of water is recognized to be the most sustainable and clean technology for the production of hydrogen (H2). Unfortunately, the efficiency is seriously restricted by the sluggish kinetics of the oxygen evolution reaction (OER) at the anode. In contrast to the OER, the electrooxidation of organic compounds (EOO) is more thermodynamically and kinetically favorable. Thus, the coupling of the EOO and hydrogen evolution reaction (HER) has emerged as an alternative route, as it can greatly improve the catalytic efficiency for the production of H2. Simultaneously, value-added organic compounds can be generated on the anode through electrooxidation upgrading. In this Minireview, we highlight the latest progress and milestones in coupling the EOO with the HER. Emphasis is focused on the design of the anode catalyst, understanding the reaction mechanism, and the construction of the electrolyzer. Moreover, challenges and prospects are offered relating to the future development of this emerging technology.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Coupling; Electrocatalysis; Hybrid Water Electrolyzer; Hydrogen Evolution; Upgrading Organic Compounds